2019
DOI: 10.1242/dev.172858
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Wnt activity on the acquisition of ectoderm potency in epiblast stem cells

Abstract: During embryogenesis, the stringent regulation of Wnt activity is crucial for the morphogenesis of the head and brain. The loss of function of the Wnt inhibitor Dkk1 results in elevated Wnt activity, loss of ectoderm lineage attributes from the anterior epiblast, and the posteriorisation of anterior germ layer tissue towards the mesendoderm. The modulation of Wnt signalling may therefore be crucial for the allocation of epiblast cells to ectoderm progenitors during gastrulation. To test this hypothesis, we exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…We then investigated directed somatic differentiation of FS cells in comparison with EpiSCs. Inhibition of the Wnt pathway shifts the character of EpiSCs toward anterior epiblast identity and predisposes them to neuroectodermal fate (Osteil et al, 2019;Tsakiridis et al, 2014). We used the Sox1::GFP reporter (Stavridis and Smith, 2003) to quantify neural induction kinetics of FS cells and EpiSCs maintained with Wnt inhibition.…”
Section: Articlementioning
confidence: 99%
“…We then investigated directed somatic differentiation of FS cells in comparison with EpiSCs. Inhibition of the Wnt pathway shifts the character of EpiSCs toward anterior epiblast identity and predisposes them to neuroectodermal fate (Osteil et al, 2019;Tsakiridis et al, 2014). We used the Sox1::GFP reporter (Stavridis and Smith, 2003) to quantify neural induction kinetics of FS cells and EpiSCs maintained with Wnt inhibition.…”
Section: Articlementioning
confidence: 99%
“…This limited neural pattern may be due to the fact that WNT levels in early-stage gastruloids and EPI aggregates are above a threshold that would promote consistent mesendodermal conversion at the expense of anterior neural progenitors. Accordingly, Osteil et al (2019) showed that embryos with increased WNT activity lose these precursors and replace them with mesoderm derivatives instead. In this work, treatment with the WNT inhibitor IWP2 resulted in a more homogeneous epiblast stem cell population and increased differentiation ability compared with ectodermal derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…We then investigated directed somatic differentiation of FS cells in comparison with EpiSCs. Inhibition of the Wnt pathway shifts the character of EpiSCs towards anterior epiblast identity and predisposes them to neuroectodermal fate (Osteil et al, 2019;Tsakiridis et al, 2014). We used the Sox1::GFP reporter (Stavridis and Smith, 2003) to quantify neural induction kinetics of FS cells and EpiSCs maintained with Wnt inhibition.…”
Section: Germline and Somatic Lineage Induction In Vitromentioning
confidence: 99%